A Molecular Compound for Highly Selective Purification of Ethylene. Issue 52 (16th November 2021) - Noonikara‐Poyil, Anurag; Cui, Hui; Yakovenko, Andrey A.; Stephens, Peter W.; Lin, Rui‐Biao; Wang, Bin; Chen, Banglin; Dias, H. V. Rasika
Abstract: Purification of C2 H4 from an C2 H4 /C2 H6 mixture is one of the most challenging separation processes, which is achieved mainly through energy‐intensive, cryogenic distillation in industry. Sustainable, non‐distillation methods are highly desired as alternatives. We discovered that the fluorinated bis(pyrazolyl)borate ligand supported copper(I) complex [(CF3 )2 Bp]Cu3 has features very desirable in an olefin–paraffin separation material. It binds ethylene exclusively over ethane generating [(CF3 )2 Bp]Cu(C2 H4 ). This molecular compound exhibits extremely high and record ideal adsorbed solution theory (IAST) C2 H4 /C2 H6 gas separation selectivity, affording high purity (>99.5 %) ethylene that can be readily desorbed from separation columns. In‐situ PXRD provides a "live" picture of the reversible conversion between [(CF3 )2 Bp]Cu(C2 H4 ) and the ethylene‐free sorbent in the solid‐state, driven by the presence or removal of C2 H4 . Molecular structures of trinuclear [(CF3 )2 Bp]Cu3 and mononuclear [(CF3 )2 Bp]Cu(C2 H4 ) are also presented. Abstract : Structurally flexible, copper scorpionate binds ethylene extremely selectively from an ethylene–ethane mixture and displays excellent performance as a reusable material for the important and challenging C2 H4 /C4 H6 separation.